COLLABORATIVE LEARNING APPROACH TO MASTER KPK AND FPB CONCEPTS: Jawa Barat, Indonesia - Nur Halizah, Zihan; Maula, Luthfi Hamdani; Efi Kurniasari (Universitas Muhammadiyah Bengkulu, 2026)
This research seeks to improve students' understanding of KPK and FPB concepts at SDN Cemerlang by addressing the constraints associated with the use of concrete media in mathematics instruction. Through the ADDIE model R&D method, Dakonball media based on Collaborative Learning was developed with 40 students. The validation results of material experts (93%), media (100%), and practitioners (93%) stated that the product is very feasible. The implementation showed a significant increase in learning outcomes, from an average of 35.13 pre-tests to 83.19 in the post-test. The results of the Paired Sample T-Test showed a significance value of 0.000, which is below the significance threshold (α = 0.05). With an N-gain of 0.73 (high category) and a positive response from students (90%), Dakonball media proved to be valid, practical, and statistically effective as an interactive mathematics learning solution in elementary schools. Keywords: Collaborative Learning; Dakonball; KPK and FPB; Elementary School